Affinity Tag Coating Enables Reliable Detection of Antigen-Specific B Cells in Immunospot Assays - Koppert, Sebastian; Wolf, Carla; Becza, Noemi; Sautto, Giuseppe A.; Franke, Fridolin; Kürten, Stefanie; Ross, Ted M.; Lehmann, Paul; Kirchenbaum, Greg A. (Cells, 2021)
Assessment of humoral immunity to SARS-CoV-2 and other infectious agents is typically restricted to detecting antigen-specific antibodies in the serum. Rarely does immune monitoring entail assessment of the memory B-cell compartment itself, although it is these cells that engage in secondary antibody responses capable of mediating immune protection when pre-existing antibodies fail to prevent re-infection. There are few techniques that are capable of detecting rare antigen-specific B cells while also providing information regarding their relative abundance, class/subclass usage and functional affinity. In theory, the ELISPOT/FluoroSpot (collectively ImmunoSpot) assay platform is ideally suited for antigen-specific B-cell assessments since it provides this information at single-cell resolution for individual antibody-secreting cells (ASC). Here, we tested the hypothesis that antigen-coating efficiency could be universally improved across a diverse set of viral antigens if the standard direct (non-specific, low affinity) antigen absorption to the membrane was substituted by high-affinity capture. Specifically, we report an enhancement in assay sensitivity and a reduction in required protein concentrations through the capture of recombinant proteins via their encoded hexahistidine (6XHis) affinity tag. Affinity tag antigen coating enabled detection of SARS-CoV-2 Spike receptor binding domain (RBD)-reactive ASC, and also significantly improved assay performance using additional control antigens. Collectively, establishment of a universal antigen-coating approach streamlines characterization of the memory B-cell compartment after SARS-CoV-2 infection or COVID-19 vaccinations, and facilitates high-throughput immune-monitoring efforts of large donor cohorts in general.
CRIS-Team WoS Importer:2021-09-03